2006
DOI: 10.1007/s11738-006-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of refinery pollution on non-enzymatic foliar defense mechanisms in four evergreen plant species in Turkey

Abstract: In order to assess the impact of SO 2 , CO 2 , NO x , and CO on non-enzymatic foliar defense mechanism around oil refineries, the present study was undertaken in Batman, Turkey during the periods February-April-June 2002. For this purpose, the four common evergreen plants at all sites, Pinus nigra Arn. subsp. pallasiana (Lamb.) Halmboe, Ligustrum vulgare L., Thuja orientalis L., and Nerium oleander L. were selected as test plants. Four study sites were selected at the Batman Refinery area (AR). Four control si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Another research showed the decreased total Chl, Chl a, Chl b concentrations and Chl a/ Chl b ratios in four evergreen plant species around the refinery, in comparison with the control sites, maybe arise from higher ambient SO 2 gas concentrations and accumulation of metals in the leaves (Deniz and Duzenli 2007). Moreover, Wang et al (2005) observed an equivalent negative effect on the Chl a and b content of rice leaves when the Chl content decreased significantly with enhanced naphthalene (one component of crude oil) stress, resulting in no significant difference in the ratio of Chl a to Chl b.…”
Section: Resultsmentioning
confidence: 97%
“…Another research showed the decreased total Chl, Chl a, Chl b concentrations and Chl a/ Chl b ratios in four evergreen plant species around the refinery, in comparison with the control sites, maybe arise from higher ambient SO 2 gas concentrations and accumulation of metals in the leaves (Deniz and Duzenli 2007). Moreover, Wang et al (2005) observed an equivalent negative effect on the Chl a and b content of rice leaves when the Chl content decreased significantly with enhanced naphthalene (one component of crude oil) stress, resulting in no significant difference in the ratio of Chl a to Chl b.…”
Section: Resultsmentioning
confidence: 97%
“…E-mail: Khromykh2012@gmail.com Вступ У міських екосистемах рослини одночасно з дією природних факторів зазнають хронічного впливу техногенних чинників, таких як сполуки важких металів, оксиди азоту та сірки, вуглеводні, феноли, пил (Slushyk, 2005;Zeiger, 2006;Yadav, 2010;Bobyliov et al, 2014), які потрапляють у рослини через забруднені повітря, воду та ґрунт. Несприятлива дія полютантів на рослини позначається скороченням періоду їх вегетації, гальмуванням ростових процесів, зменшенням площі асиміляційних органів (Wierzbicka and Obidzinska, 1998;Bezsonova, 2001), зниженням вмісту фотосинтезувальних пігментів у листках (Deniz and Duzenli, 2007;Garifzyanov and Ivanyschev, 2011), порушенням фізіологічних і біохімічних регуляторних систем (Kulagin, 2002;Ramel et al, 2012). За дії стресорів онтогенез рослин забезпечується винятково за рахунок активації захисних ресурсів на різних рівнях організації рослинних організмів (Polle, 2000;Zang and Gallie, 2005;Kolupaev and Karpets, 2010), що зумовлює їх адаптацію до несприятливих умов середовища.…”
Section: дніпропетровськийunclassified
“…Anthropogenic impact on plant communities is an urgent problem for Dnipropetrovsk, where the volume of industrial emissions accounts for 17% of Ukraine's total emissions (Pakhomov and Brygadyrenko, 2005), currently reaching more than 1 million tons per year (Striletz, 2015;Tsvetkova et al, 2016). The adverse effect of pollutants can manifest itself in various functional changes in trees such as a decrease in the photosynthetic pigment content of leaves (Deniz and Duzenli, 2007), or failure of the physiological and biochemical mechanisms regulating vital functions (Ramel et al, 2012). As Gill and Tuteja (2010) have found, the activation of plant protective mechanisms belonging to different levels of plant organization, has a crucial role in the formation of resistance to the action of abiotic stressors.…”
Section: Introductionmentioning
confidence: 99%